Bovine besnoitiosis (Besnoitia besnoiti) in an Irish dairy herd. (11th June 2016) - Ryan, E. G.; Lee, A.; Carty, C.; O'Shaughnessy, J.; Kelly, P.; Cassidy, J. P.; Sheehan, M.; Johnson, A.; de Waal, T.
Abstract : Bovine besnoitiosis, caused by the apicomplexan protozoan parasite Besnoitia besnoiti, was diagnosed in an Irish dairy herd. This is the first diagnosis of besnoitiosis in Ireland or the UK and the most northerly European outbreak yet described. The diagnosis occurred following a farm investigation in June 2015 into an unusual dermatological problem that had been ongoing since 2010. On an annual basis, 1–2 per cent of cows in the herd exhibited clinical signs, including skin thickening, alopecia, weight loss and poor performance. Others displayed pyrexia, limb oedema, respiratory distress and reduced milk yield. Histopathological examination of skin revealed granulomatous and eosinophilic dermatitis, with characteristic intradermal protozoal cysts, consistent with cutaneous besnoitiosis. Follow‐up serological testing and clinical examination of cattle (n=228) on the farm found that 68 per cent (144/212) were seropositive for B. besnoiti . In addition, 51 per cent (117/228) had characteristic scleral conjunctival cysts and 68 per cent (134/198) had vulval cysts. Postmortem examination of a severely affected animal revealed typical gross and histopathological lesions of B. besnoiti infection. These results confirmed endemic infection with B. besnoiti . The identification of this exotic disease highlights the importance of veterinary surveillance at both local and national level, particularly in relation to emerging diseases.